HIDDEN CURRICULUM IN STUDENTS’ ACTIVITIES AT MODERN ISLAMIC BOARDING SCHOOL: Phenomenology Study at Darussalam Gontor Islamic Boarding School, Ponorogo, East Java - Alamin, Nurul Salis; Rahmawati, Zakiya Setyo; Maha, Marheni Br; Nisa, Shofiyyatun; Zalzuli, Ahmad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
The dynamics of santri activities at Pondok Modern Darussalam Gontor make it possible to implement the hidden curriculum holistically and make it possible to implement it holistically and comprehensively. It is proven that this institution has produced quality alumni, taking part in the community, both nationally and internationally. Therefore, the purpose of this study is to reveal the success of the pesantren in shaping the character of students behind the activities of students contained in the hidden curriculum. The research method used is a qualitative method with a phenomenological approach. To obtain data holistically and integratively, this research uses three techniques, namely; in-depth interviews, participant observation and documentation studies. Data analysis techniques used from Milles & Huberman. The results of this study indicate that the hidden curriculum in the education system at Pondok Modern Darussalam Gontor is found in the activities or activities of santri, both intracurricular, co-curricular, and extracurricular. It can be concluded that the hidden curriculum in it has a strong relationship with holistic leadership ranging from mindset leadership from mindset, attitude (behavior), to leadership skills.Keywords: Hidden Curriculum; Islamic Boarding School; Leadership; Student Activities; Islamic Education.